The effect of normal and abnormal eddies on the mixed layer depth in the global ocean - Hao, Ji; Yang, Jie; Chen, Ge (Frontiers in Marine Science, 2023)
Mesoscale eddies are broadly distributed over the global ocean and play a significant role in modulating the spatiotemporal evolution of mixed layer depth (MLD). The presence of abnormal eddies in the ocean has been shown; however, the precise quantification of the effect of eddies on MLD, given the case of abnormal eddies, has not been carried out thus far. Differently from the previous approach to identify abnormal eddies through sea surface temperature, we therefore, proposed a method to identify abnormal eddies, using potential density based on Argo data (Array for Real-time Geostrophic Oceanography) for 15 years from 2003 to 2017. Results showed that abnormal anticyclonic eddies (AAE) and abnormal cyclonic eddies (ACE) accounted for 21.67% and 20.17% of total matching anticyclonic eddies (TAE) and the total matching cyclonic eddies (TCE), respectively, in the global ocean. The proportions of abnormal eddies were relatively higher in tropical regions but lower in regions with the boundary current and strong eddy kinetic energy. The MLD changes caused by normal and abnormal eddies were estimated combining satellite altimetry data. The normal eddies were the total matching eddies with the removal of the abnormal eddies, separately called normal anticyclonic eddies (NAE) and normal cyclonic eddies (NCE). The overall influence of NAE (NCE) was more significant on MLD deepening (uplifting) than that of TAE (TCE). Globally, NAE (NCE) changed MLD deepening (uplifting) from ~66 m (~54 m) to ~67 m (~53 m) and exhibited a more pronounced change in the Indian Ocean sector of the Southern Ocean region, from ~111 m (~94 m) to ~115 m (~92 m) in the winter. AAE (ACE), exerted a relatively weak but opposite effect on MLD deepening (uplifting). In other words, the global average MLD caused by them shoaled (deepened) from ~66 m (~54 m) to ~59 m (~59 m), and the North Pacific Ocean shoaled (deepened) from ~61 m (~47 m) to ~49 m (~57 m) in winter. Given the above results, abnormal eddies should be accounted for when the impact of ocean eddies is evaluated on the global climate system.